PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN SAMPAH ORGANIK DI KELURAHAN TAMBAK SARIOSO KOTA SURABAYA MELALUI INOVASI ECO ENZYME - Cornelis, Vieta Imelda; Sucipto, Sucipto; Damayanti, Sri Sukmana; Sidarta, Dudik Djaja; Baruno, Agustiawan Djoko; Ayu Chyntia, Desak Nyoman; Kayla Natasha, Amanda; Rohman Bulu, Akbar Taufiqur; Mulyosudarmo, Suviana Suwoto; Rahmah, Nabila Aliya (Batara Wisnu : Indonesian Journal of Community Services, 2025)
Household organic waste management remains a serious problem in urban areas, including in Tambak Sarioso Village, Surabaya City. The high volume of organic waste, low level of waste sorting at source, and limited community participation indicate a gap between normative regulations and the implementation of waste management policies. This condition necessitates research, considering that waste management is directly related to environmental protection and the fulfillment of the community's right to a healthy environment. This study aims to analyze the empirical conditions of organic waste management in Tambak Sarioso Village and to examine the implementation of eco-enzymes as a community empowerment strategy within the legal framework of waste management. The main research question focuses on the effectiveness of eco-enzymes in bridging legal norms and social practices of household-based organic waste management. The results show that organic waste management in Tambak Sarioso is not yet optimal due to low legal awareness and limited supporting facilities. The implementation of eco-enzymes has been proven to increase community participation, reduce organic waste generation, and improve the quality of the residential environment. These findings contribute to strengthening the concept of community empowerment as an instrument of environmental law effectiveness. The research conclusion confirms that eco-enzymes are an innovative model of community-based organic waste management that is relevant for strengthening the implementation of waste policies. The novelty of this research lies in the integration of empirical, normative, and community empowerment approaches into a single framework of sustainable waste management.